2020
DOI: 10.1038/s41467-019-14210-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing electron transfer reactions and catalysis in multicopper oxidases with operando X-ray absorption spectroscopy

Abstract: Here we propose an experimental setup based on operando X-ray absorption spectroscopy (XAS) to understand why copper-containing oxidoreductase enzymes show exceptional performance as catalysts for the oxygen reduction reaction (ORR). An electrode based on carbon nanoparticles organized in mesoporous structures with bilirubin oxidase (BOD) was developed to be used in a home-made operando XAS electrochemical cell, and we probed the electron transfer under ORR regime. In the presence of molecular oxygen, the BOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…(Christenson et al, 2006;Schubert et al, 2009;Tsujimura et al, 2005b) The second redox couple with E o equal to 0.16 V is in good agreement with the data reported for reduction and oxidation of the T2/T3 Cu center of the enzyme, (Ivnitski et al, 2008) which acts as an electronic bridge in the internal electron transfer mechanism to promote the reduction of dioxygen. (Macedo et al, 2020) As previously reported, the peaks corresponding to reduction and oxidation of the T1 Cu site are less defined in neutral media as a result of the change of bond length between this Cu atom and the ligand groups and the special arrangement of this site. (Ivnitski et al, 2008;Ramírez et al, 2008) These results indicated an efficient direct electrical communication between the enzyme and the carbon nanoparticles, which is usually desirable in enzyme-based BFCs and biosensors.…”
Section: Bioelectrochemical Performance Of Bod-based Biogel/c Electrodementioning
confidence: 61%
See 2 more Smart Citations
“…(Christenson et al, 2006;Schubert et al, 2009;Tsujimura et al, 2005b) The second redox couple with E o equal to 0.16 V is in good agreement with the data reported for reduction and oxidation of the T2/T3 Cu center of the enzyme, (Ivnitski et al, 2008) which acts as an electronic bridge in the internal electron transfer mechanism to promote the reduction of dioxygen. (Macedo et al, 2020) As previously reported, the peaks corresponding to reduction and oxidation of the T1 Cu site are less defined in neutral media as a result of the change of bond length between this Cu atom and the ligand groups and the special arrangement of this site. (Ivnitski et al, 2008;Ramírez et al, 2008) These results indicated an efficient direct electrical communication between the enzyme and the carbon nanoparticles, which is usually desirable in enzyme-based BFCs and biosensors.…”
Section: Bioelectrochemical Performance Of Bod-based Biogel/c Electrodementioning
confidence: 61%
“…The deposition of matter along the original drop edge after the evaporation of a solvent is known as the coffee-ring effect. (Mampallil and Eral, 2018) This phenomenon has been reported during the redox enzyme immobilization (Li et al, 2018) and happens during the solvent evaporation, when the edges of the drop become pinned to the solid substrate, and the outward capillary flow from the center of the drop brings the nonvolatile component to the edge of the droplet. (Crivoi and Duan, 2013) Characteristics similar to those of the BOD-based biogel and bare-BOD films immobilized on the gold substrate are also obtained for the glassy carbon (GC) platform; the BOD-based biogel film (Fig.…”
Section: Bod-based Biogel Homogeneitymentioning
confidence: 81%
See 1 more Smart Citation
“…Methods allowing mass or layer thickness quantification, i.e., SPR, QCM-D and ellipsometry, coupled to electrochemistry will give access to the relationship between enzyme loading or release and catalytic response [21,116,271,272,311]. Electrochemistry coupled to spectroscopies (IR (including SEIRA, PMIRRAS), XAS, fluorescence, Raman (including SERRS), EPR, CD, mass spectrometry) will help in the determination of conformational change once enzyme is immobilized or as a function of applied potential or current [312][313][314][315][316][317]. Microscopy coupled to electrochemistry will allow the mapping of the electrocatalysis [318][319][320].…”
Section: Discussionmentioning
confidence: 99%
“…Within the vast number of spectroscopies, some are more commonly used for in situ and operando measurements, such as Fourier transform infrared (FTIR) spectroscopy that provides information on the vibrational modes of covalent bonds within a given molecule, [4] while X‐ray absorption spectroscopy (XAS) provides information on the oxidation state of redox co‐factors and their chemical environment/coordination sphere [5] . Raman spectroscopy, another powerful vibrational spectroscopic technique, is widely used for the chemical and structural characterization of biomolecules and studies the inelastic interaction of molecules with monochromatic light, usually emitted by a laser source in the visible, near‐IR, or near‐ultraviolet (UV) range [6] .…”
Section: Introductionmentioning
confidence: 99%